The artificial neutrophil and a proposal of an in silico research of the immune response in human bacterial diseases - DOI 10.5752/P.2316-9451.2014v2n2p79 - Siqueira-Batista, Rodrigo; Souza, Flávio Oliveira de; Gomes, Andréia Patrícia; Oliveira, Alcione de Paiva; Oliveira, Izabella Soares de; Farago, Willian Cordeiro; Bastos, Carlos Antônio; Possi, Maurílio de Araújo; Santana, Luiz Alberto; Cerqueira, Fábio Ribeiro (Abakós, 2014)
Bacterial diseases are important conditions in human medicine. First, because of the epidemiological impact, and, second, due to the gravity of some of these infectious processes. It is worth to highlight bacterial sepsis and acute bacterial meningoencephalitis which are morbid conditions that can lead to death in a short period of time. In this context, neutrophils are extremely important cells in the interaction man/bacteria although many aspects of the performance of these cells remain awaiting elucidation. This paper presents the requirements for computational simulation of neutrophils in the AutoSimmune system and some preliminary description of the activity of this kind of cell in post-streptococcalglomerulonephritis, a major human disease that affects the kidneys. The preliminary results presented here is the support for further development of in silico studies on the role of neutrophils in bacterial diseases.